A nanoprecursor method for successfully synthesizing clinoptilolite with high-crystallinity and resultant effects on CO2/CH4 selective adsorption. Issue 49 (15th September 2021) - Zhai, Chengwei; Sun, Jihong; Jia, Bingying; Gul, Anadil; Bai, Shiyang
Abstract : Nanoprecursors used as a structural promoter (SP) were prepared by a hydrothermal method and named sol-SP. Abstract : Nanoprecursors used as a structural promoter (SP) were prepared by a hydrothermal method and named sol-SP. After centrifugation, the supernatant and precipitate were denoted as solution-SP and solid-SP, respectively. The effect of the additive amount on the structures and properties of the synthesized clinoptilolite was investigated using various characterization techniques. The activation energies of crystallization kinetics during induction and growth periods were calculated. The results showed that the induction period is the control step during the synthesis of clinoptilolite, while additive sol-SP or solid-SP was beneficial to shorten the induction period and therefore enhance the formation of the crystal nucleus. When their pre-crystallization time was too long or the additive amount was too much, the impure phase (phillipsite) in the synthesized clinoptilolite was easily generated. Although the addition of solution-SP had no obvious effect on the induction period, it promoted the growth of crystals after nucleation. Finally, the adsorption performances for CO2 and CH4 were preliminarily assessed using synthetic clinoptilolite as the adsorbent, showing the promising application for the separation of CO2 /CH4 .